Spinal Cord Stimulation as an Alternative to Opioid for Axial Neck and Back Pain: A Case Series - Mullins, Graeme Sampson; Burns, Joanna Jane; Schneider, Andre Perillier; El Helou, Antonios (Frontiers in Pain Research, 2022)
Introduction Spinal cord stimulation is emerging as a minimally invasive technique for treatment of persistent spinal pain syndrome (PSPS). Methods We describe a case series of 25 individuals with PSPS who underwent implantation of a spinal cord stimulator device between 2017 and 2021. Results There was a significant reduction in mean visual analog scale pain scores in the immediate postoperative phase, (8.61 vs. 2.3, p < 0.001). There were twelve patients who consumed pre-operative opioid, and 75% showed reduction of use with a significantly lower average daily dose (66.8 vs. 26.9 meq/D, p < 0.05). There was a significant reduction in the Oswestry Disability Index during postoperative follow-up visits (p < 0.001). There were no major perioperative or long-term complications from the procedure in follow-up. Conclusion The analysis of this cohort suggests successful long-term treatment of a diverse set of patients with PSPS who underwent spinal cord stimulation (SCS) and had meaningful improvement in quality of life and reduction in opioid consumption.